Pengaruh Kebiasaan Belajar dan Bimbingan Orang Tua Terhadap Prestasi Belajar Siswa Kelas AtasDi SDN 04 Tegalgede Tahun 2015/2016 - Septiana, Erma, Drs. Suwarno, SH., M. Pd (2016)
The purpose of this study is to determine: (1) The effect of study habits on student achievement in SDN 04 Tegalgede year 2015/2016(2) The effect of parental guidance on student achievement in SDN 04 Tegalgede year 2015/2016(3) Effect between study habits and guidance of parents on student achievementin SDN 04 Tegalgede year 2015/2016. Quantitative research with survey design, the subject of his research is the class (IV, V, VI) with 45 students with Proportionate Stratified Random Sampling technique. Data collection techniques such as questionnaires engineering, documentation and interviews. Data were analyzed using multiple linear regression techniques, t test, F test, test of determination, SR (Relative Contribution) and SE (Effective Contribution). The results showed (1) there is influence between study habits and guidance of parents on student achievement in SDN 04 Tegalgede year 2015/2016to the regression equations 40.570 + 0.215 X1 + 0.389 X2, where the significance of the effect indicated by F count (24.176)> F table (3.22), (2) there are significant study habits on student achievement as indicated in SDN 04 Tegalgede year 2015/2016by the t (2.334)> t table (2.018), (3) there are significant parental guidance on student achievement as indicated in SDN 04 Tegalgede year 2015/2016by the t (4.431)> t table ( 2.018)study habits and guidance of parentsmore dominant variablesguidance of parents.This is shown with the SR study habits(32,3%) > SRguidance of parents(67,6%), SEstudy habits(17,2%) > SEguidance of parents(35,9%). Keywords : Study Habits , Parental Guidance , Learning Achievement